Inverse design of a high‐quality factor multi‐purpose optical biosensor. Issue 6 (10th March 2022) - Mafi, Majid; Esmaile, Amir Hosn
Abstract: This paper investigates a high‐quality and multi‐purposed biosensor with maximum stable output transmittance numerically by using the inverse design method. The proposed biosensor utilises particle swarm optimisation for inverse design which will be a helpful way of designing different kinds of precise sensors in the future. In this research, some parameters are introduced to the optimiser to find the best cavity parameters for developing a high‐quality sensor to sense different targets. Many previous studies were on single‐goal biosensors, or their quality factor and output spectrum were very low. The proposed sensor can sense different parts of blood components, the amount of glucose in the urine, and tear's glucose for the first time just in one device to the best of our knowledge. Compared to previous works, this structure detects the differences between refractive indexes analytes with a high‐quality factor and a high and stable output transmittance spectrum. This structure contains two‐dimensional photonic crystal microresonators to provide resonance frequencies in the photonic bandgap. The device works on a window of 1.55 μm with a quality factor equal to 24, 000, the sensitivity is 500 nm/ RIU (refractive index unit), and the resolution is equal to 4 × 10 −5 . In this paper, the scaling method, particle swarm optimisation, two‐dimensional finite‐difference dime domain, and Plane‐Wave Expansion methods are utilised.